Defect reduction in m-plane GaN on m-sapphire via lateral epitaxial overgrowth by hydride vapor phase epitaxy - 김민호; 우서휘; 소병찬; 심광보; 남옥현 (Journal of ceramic processing research, 2016)
We report on the improvement of the structural and optical properties of m-plane GaN layers on m-plane sapphire viaepitaxial lateral overgrowth (ELO) using hydride vapor phase epitaxy. The planar m-plane GaN was compared to ELO mplaneGaN with stripes patterned along the [1120] and [0001], respectively. The ELO m-plane GaN samples showed narrowx-ray rocking curves and more improved cathodoluminescence (CL) images compared with those of the planar m-plane GaN. The density of threading dislocations (TDs) and basal-plane stacking faults (BSFs) was decreased in the ELO m-plane GaN,which was confirmed by transmission electron microscopy (TEM) and Williamson - Hall (W-H) plot analysis. KCI Citation Count: 3